The new zinc phthalocyanine having high singlet oxygen quantum yield substituted with new benzenesulfonamide derivative groups containing schiff base - Piskin, Mehmet; Canpolat, Erdal; Ozturk, Omer Faruk (Elsevier, 2020)
The new (E)-4-((5-bromo-2-hydroxy-3-methoxybenzylidene)amino)-N-(5-methyl-1,3,4-thiadiazol-2-yl) benzenesulfonamide 1, (E)-4-((5-bromo-2-(3,4-dicyanophenoxy)-3-methoxy benzylidene)amino)-N-(5-methyl-1,3,4-thiadiazol-2-yl)benzenesulfonamide 2 and peripheral tetrakis-(E)-4-((5-bromo-3-methoxy-2-(lambda(1)-oxidaneyl)benzylidene) amino)-N-(5-methyl-1,3,4-thiadiazol-2-yl)benzenesulfonamide substituted zinc(II) phthalocyanine 3 were been synthesized and characterized using UV-vis, FT-IR, H-1 NMR, C-13 NMR (except for 3), MALDI-TOF mass spectra and elemental analysis for the first time. The spectroscopic, photophysical and photochemical properties for the phthalocyanine 3 were been described in dimethyl sulfoxide. These properties of the phthalocyanine 3 as a photosensitizer are very useful for photodynamic therapy application and its good fluorescence properties, high singlet oxygen quantum yield and appropriate photodegradation quantum yield are very important for Type II mechanisms. It has the remarkable potential to be used as Type II photosensitizers for the treatment of cancer in photodynamic therapy with these features. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: sulfa drugs; phthalocyanine; photophysical; photochemical